Gravity balanced compliant shell mechanisms. (July 2017) - Radaelli, G.; Herder, J.L.
Highlights: A compliant shell mechanism is designed that statically balances its own weight and an additional payload. The load-displacement response is tailored by using shape optimization. The design procedure can be used to create novel compliant shell mechanisms. Two vacuum-formed physical demonstrators of an optimized shell have been constructed and tested. Abstract: The research on compliant shell mechanisms is a new and promising expansion of the well established compliant mechanisms research area. Benefits of compliant shell mechanisms include being spatial and slender, having organic shapes and their high tailorability of the load-displacement response. This work focusses on the design of a shell with tailored force output at large deformations by means of a shape optimization procedure. The procedure is applied to create a statically balanced mechanism where the self-weight of the shell and an additional payload is balanced by the elastic forces of the deforming shell. The optimization is based on an isogeometric numerical simulation. A physical demonstrator is constructed by vacuum forming a PETG polymer sheet. The result of a force measurement on the prototype shows a good qualitative match, although quantitatively the discrepancies are substantial.